Prediction Financial Distress in The Influence of Indonesian Banking Camel Ratio - Azaluddin (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2023)
This study aims to analyze the effect of financial ratios CAR (Capital Adequacy Ratio), NPL (Non Performing Loan), ROA (Return on Assets), ROE (Return on Equity), BOPO (Operational Cost/Operational Income), LDR (Loan to Deposit Ratio) to financial distress bankingin 2016- 2019. The example of this study used purposivesampling as many as 9 companies in accordance with predetermined criteria with a research period of 2016- 2019, informasi obtained from the Indonesia Stock Exchange (IDX). The analytical method used to test the research hypothesis is logistic regression. The results showed that the financial ratios of CAR, NPL, ROA, ROE, BOPO and LDR had predictive power for the condition of banks experiencing financial distress. The resulting regression equation is Y= 924, 779 -17, 499 CAR+ 6, 186 NPL+ 39, 350 ROA 32, 091 ROE+ 8, 081 LDR– 25, 516 BOPO. The results of the clarification partially show that the CAR, BOPO and LDR variables have a negative and significant result on financial distress. While the variables NPL, ROA serta ROE have a positive but not significant effect on financial distress.